El pensamiento gráfico y el patrimonio construido de la UNLP - Carbonari, Fabiana Andrea (2018)
The researches about the buildings of the National University of La Plata have been in development for a long time and address different issues. Graphic thinking is taken from drawings as a documentary source but, in none of them, a detailed study of the history of university education has been made from their graphic productions. This work proposes to reflect and disseminate the progress of two work plans carried out in the investigation Project “Spatial Conception and Graphic Thinking. The history of the National University of La Plata through the graphic language -1905-2015-“ based in the Graphic Experimentation Laboratory of Habitat relating the influence of drawing and the architectural heritage of the UNLP.